Cleft Lip/Nasal Deformities After Plastic Surgery for Unilateral Cleft Lip/Palate: A Prospective Study at a Large Hospital in Vietnam [Corrigendum] - Nguyen HL; Nguyen VM; Tran XP (Dove Medical Press, 2023)
Nguyen HL, Nguyen VM, Tran XP. Clin Cosmet Investig Dent. 2021;13:305–314. The authors wish to advise that the study reported in the published article was previously described in the Vietnamese publication: Nguyễn Văn Minh, Trần Tấn Tài, Nguyễn Hồng Lợi (2018). Đánh giá những biến dạng môi mũi bệnh nhân sau tạo hình khe hở môi một bên lần đầu. Tạp chí Y Dược học - Trường Đại học Y Dược Huế - Tập 8, số 5, Trang 65-71. Link: http://jmp.huemed-univ.edu.vn/BBao/2020/3/PDF_2020m03d016_9_5_4.pdf. The author lists are different between the two versions because the English version was written independently of the previous Vietnamese publication and contained updated information.